2000
DOI: 10.1590/s0066-782x2000000100004
|View full text |Cite
|
Sign up to set email alerts
|

The results of the Campaign for evaluating sphygmomanometers accuracy and their physical conditions

Abstract: Objective -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Defects were found in 68 valves (18%), 114 (32%) inflatable bladders, and also in inflation bulbs; these rates are unacceptable and lead to inadmissible BP reading errors. Other authors 8,9 evaluated the functioning of sphygmomanometers in different situations and also found inadequate conditions. For this reason, assessment of calibration and functioning of these devices is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Defects were found in 68 valves (18%), 114 (32%) inflatable bladders, and also in inflation bulbs; these rates are unacceptable and lead to inadmissible BP reading errors. Other authors 8,9 evaluated the functioning of sphygmomanometers in different situations and also found inadequate conditions. For this reason, assessment of calibration and functioning of these devices is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Bailey and his group [13] defined their manometers intolerant if the limit was AE3 mmHg at two or more of the five test points. In the reports of Mion et al [4,5], manometers employed by private practice physicians as well as those from hospitals were used in the same trials with the devices of the former group having a lower level of accuracy (Tab. 4).…”
Section: Resultsmentioning
confidence: 99%
“…This accomplishment, and indeed the whole idea of blood pressure measurement, met with disapproval by the British Medical Journal which expressed the view that, when using sphygmomanometry, we pauperise our senses and weaken clinical acuity [2]. In any case, although some 130 years have passed since the invention and in spite of technical improvements made on it, several studies have shown that more than fifty percent of aneroid manometers in hospitals are unacceptably erroneous [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Velcro-type clamps increase the chance of the device being calibrated by approximately six times. This issue can be approached as a factor of the efficiency and ease of Velcro in keeping in the patient's arm, unlike the clamp that has points predetermined to be fixed, generating spaces and possible gaps which can generate problems in the measurement of blood pressure that can be compared to the use of arm rests of inadequate arm circumference [17,18] . Table 9 Analysis of the type of apparatus in relation to the quantity of calibrated.…”
Section: Discussionmentioning
confidence: 99%